2016
DOI: 10.1177/1971400915621324
|View full text |Cite
|
Sign up to set email alerts
|

Characteristic brain MRI findings in ataxia-neuropathy spectrum related to POLG mutation

Abstract: Patients with mutations in the polymerase gamma gene (POLG) may present with progressive ataxia and in such situations neuroimaging findings may suggest the diagnosis. Herein we report a patient with a POLG gene W748S homozygous mutation and characteristic lesions in the thalamus, cerebellum and inferior olivary nucleus seen on magnetic resonance imaging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 12 publications
0
10
0
1
Order By: Relevance
“…11 POLG is involved in mitochondrial DNA repair in the neurons, while mutation of this gene causes neurodegeneration. 12 SLC38A2 is a fundamental part of BBB and plays an integral role in glutamine transport in neurons. 13 GABARALP2 mediates inhibitory neurotransmission.…”
Section: Discussionmentioning
confidence: 99%
“…11 POLG is involved in mitochondrial DNA repair in the neurons, while mutation of this gene causes neurodegeneration. 12 SLC38A2 is a fundamental part of BBB and plays an integral role in glutamine transport in neurons. 13 GABARALP2 mediates inhibitory neurotransmission.…”
Section: Discussionmentioning
confidence: 99%
“…Central nervous system Dysarthria none [7] Dysphagia ANT1/POLG1 [4] Tremor POLG1 [10] Cognitive impairment POLG1 [10] Dementia POLG1 [10] Epilepsy none [11,12] Olivary degeneration POLG1 [13] Parkinsonism POLG1 [14] Headache POLG1 [12] Lactate elevation ANT1/POLG1 [4,12] Depression POLG1 [6] Anxiety POLG1 [6] Eyes Visual impairment POLG1 [10] Ears Impaired hearing ANT1/POLG1 [4] Endocrine organs Early menopause POLG1 [6] Heart Sudden cardiac death POLG1 [1] Gastrointestinal tract Constipation (MNGIE-like) POLG1 [6] Peripheral nerves Sensory ataxia POLG1 [10] Gait disturbance/falls ANT1/POLG1 [4] Sensory-motor neuropathy POLG1 [10] Muscle Ptosis POLG1 [6] Ophthalmoparesis POLG1 [10] Quadruparesis ANT1/POLG1 [4] Muscle cramps POLG1 [6] Lactic acidosis ANT1/POLG1 [4]…”
Section: Manifestationmentioning
confidence: 99%
“…Patients with SANDO typically show cerebellar atrophy, and fissures and hyperintense lesions in the olivary nuclei, cerebellar white matter, and the dorsomedial thalami [7]. Did the patient undergo a second cerebral imaging for followup and were these typical abnormalities detectable on MRI?…”
mentioning
confidence: 99%
“…These events ensured that virtually all POLG protein in the cell derived from the A467T allele, leading to haplotype insufficiency and severe Alpers syndrome in early childhood (Chan et al 2009; Chan et al 2005b). However, patients homozygous for A476T or W748S can develop a wide range of mitochondrial diseases, from early onset Alpers syndrome to mid-age onset ataxia neuropathy syndrome to adult onset progressive external ophthalmoplegia (Bereau et al 2016; Blok et al 2009; Gonzalez-Vioque et al 2006; Henao et al 2016; Lax et al 2012; McHugh et al 2010; Rajakulendran et al 2016; Tang et al 2011). We also found that single nucleotide polymorphisms can play a role in modulating disease.…”
Section: Origins and Consequences Of Mtdna Instabilitymentioning
confidence: 99%